The historical center of Pisaq, heritage valuation and current review - Chalco, Anli (2018)
This article is part of an investigation related to the management of the built heritage, with special attention in the Peruvian cases, enriched by the crossing of disciplinary perspectives on archeology, architecture, conservation of built heritage and urban management -cultural versus urban development and the negative impact on the urban landscape. It is therefore a research in process, which aims to be a far-reaching reflection on the potentialities of the territory-heritage binomial, achieved through photographic registration, review and compilation of documentary and planimetric sources. The case was developed in the district of Pisaq, which currently owns a very traditional historic center that preserves an urban layout in the form of checkerboard and an architecture belonging to the Vice royal and Republican period, all located on a system of Inca terraplens. Expressing in this way very unique characteristics that reflect a perfect integration between man and nature.